STP Revision Which Leads to Change on Business Model and Marketing Strategy of BRIGANDINE with The Purpose of Expanding The Market Share (The Indonesian Journal of Business Administration, 2013)
Football industry Indonesia is currently on the rise and got a lot of public attention. As a result of increasing interest in the sport, many opportunities have opened up. One is the opportunity to market the complementary product to perform activities of playing football / Futsal such as the jersey. Brigandine Football is a startup company that creates football/Futsal sportswear. Brigandine was founded in late 2011.There are few issues that brigandine face, the biggest problems is the lack of sales & promising future market. The step that we will take to find the root cause are to do internal an external analysis, The purpose of internal analysis is to know the weaknesses & strength of the company. And, The purpose of the external analysis is to find out the external factor of the business that can influence the company. From the analysis, find out that there are 3 root causes, they’re: 1) The pricing strategy is not suitable (pricing is higher than competitors). 2) The lack of physical store. 3) The lack of product extension, service and warranty. The sequence of problem solving for brigandine starts with the revision of STP. This revision made because the behavioral factor that is different from the survey and the STP that brigandine has, so it need some adjustment to fit into the segment that already shaped by the market. And then followed by the revision of business channels. After the revision of business model, we will try to give solution for brigandine problem. The first one is choosing the type of physical stores, continued with the addition of product extension/services/warranty. And then finally, the revision of pricing strategy for brigandine. The STP revision is in the targeting and positioning area. While the changes in the business model are in customer segment, value proposition, channels, and customer relationship. The solutions gives to Brigandine root cause is choosing the mobile store as their official store, the addition of product extension in terms of Armless Jersey, Long sleeve Jersey, Training Vest, Jersey for kids & additional service in terms of Number printing service. And the last is choosing a promotional price strategy and discount & allowances as the pricing strategy to expand the market share of Brigandine. Keywords: physical store options, additional product extension/services/warranty, pricing strategy.